27 Anxiety in paediatric patients: a summary of routinely recorded data at GOSH. (23rd February 2023) - Chandran, Anchit; Bowyer, Stuart A; Pissaridou, Eleni; Booth, John; Briggs, Lydia; Bryant, William A; Key, Daniel; Shah, Mohsin; Spiridou, Anastassia; Sebire, Neil J
Abstract : Aims: We performed an analysis of GOSH's Electronic Patient Record (EPR) data derived insights relating to patients diagnosed with an ICD-10 anxiety code. This analysis examined trends in frequency distribution and duration of anxiety diagnoses over time, alongside the medication administrations and procedures performed on these patients. Methods: Routine data for all patients diagnosed with an ICD-10 anxiety code ( F41- ) from July 2019 to March 2022 were extracted, de-identified, and analysed in the secure GOSH Digital Research Environment (DRE). The Python package Pandas was used to clean and analyse data. Interactive visualisations were created using Plotly . Medication drug classes for these patients ( Hypnotics, Anxiolytics, and Antidepressants ), and OPCS-4 -classification-identified-procedures were analysed. Results: Across 1573 patients in the cohort, 'Anxiety disorder, unspecified' ( F419 ) was the most common anxiety type until 2021, gradually being replaced by 'Other specified anxiety disorders' ( F418 ). The monthly sum of anxiety diagnoses demonstrated a seasonal variation, peaking in July 2019 and July 2021, with a trough spanning UK COVID-19 lockdowns. Chronic Kidney Disease, Autism, and other developmental disorders were the most prevalent comorbidities. Stratifying by drug class, Hypnotics & Anxiolytic administrations were more popular than Antidepressants for patients diagnosed with anxiety. Melatonin was the most administered medication. The OPCS-4 Class ' U ' ( 'Diagnostic imaging, testing and rehabilitation' ) was the most common group of procedures performed on the same day as an anxiety diagnosis. Transthoracic Echocardiography and CSF Injection were most prevalent. Conclusion: This analysis of EPR data found a seasonal variation in anxiety diagnosis frequency, with a gradual change in the specific type. Hypnotics & Anxiolytics are more popular than Antidepressants . Anxiety diagnoses relate mostly to imaging and testing procedures. Further work includes the same analyses and trends on earlier data.